2016
DOI: 10.1097/md.0000000000005041
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal association between hemoglobin concentration and hypertension

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
3
13
0
1
Order By: Relevance
“…Age, BMI, and hemoglobin level, which showed an increase in progression in both males and females, can be applied as the observed indicator of the progression, even in the normotensive period. In agreement with our results, there is considerable evidence of these factors as a possible risk factors of hypertension [16,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…Age, BMI, and hemoglobin level, which showed an increase in progression in both males and females, can be applied as the observed indicator of the progression, even in the normotensive period. In agreement with our results, there is considerable evidence of these factors as a possible risk factors of hypertension [16,[24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to other studies , risk of pre‐HT and HT increased with increasing Hb levels. The biological mechanisms that explain the link between high Hb level and high BP are unclear, but increased blood viscosity, activation of renin‐angiotensin‐aldosterone system and variation in erythropoietin secretion have all previously been suggested .…”
Section: Discussionsupporting
confidence: 89%
“…Finally, both pre-HT and HT and haemoglobin (Hb) levels affect pregnancy outcomes [17] and there are indications that both SBP and DBP may increase with increasing Hb levels. This association has been widely investigated among Caucasians and Asians but with conflicting results [20][21][22][23][24]. Few studies among Africans have all shown a positive association between increasing Hb with BP [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This was consistent with previous reports that low hemoglobin/hematocrit levels in the general population may be associated with a higher risk of ESRD, while hemoglobin-related improvements of outcomes were reduced in people with excessively higher hemoglobin levels [11,12]. This may be partly explained by the association between elevated hemoglobin levels and higher blood pressure [40][41][42] which is a risk factor for CKD progression. In the present study, hemoglobin levels correlated positively to mean atrial pressure (male: r = 0.10, p = 0.004; female: r = 0.12, p < 0.001).…”
Section: Discussionsupporting
confidence: 92%